(untitled) (Journal of the College of Basic Education, 2022)
The technical development that produced the Internet is a very big leap in the development of the means of mass communication, and the emergence of social networking sites represented an intense reinforcement of this development, which made this modern means an effective means of communication in all fields, including the political field, and specifically the field of parliamentary elections, in which the owners of the legitimate authority are determined. In leading countries and peoples.The research problem in this context was identified by a major question about the role of social networking sites in activating participation in the Iraqi parliamentary elections that took place in 2014? The importance of research on this topic stems from the importance of knowing the reasons that drive the public to rely on social networking sites to obtain information